A arte como recurso para potencializar a aprendizagem significativa - Oliveira, Cláudia Regina Melo de (2020)
Literacy is one of the most important achievements in life. When there is interference in this process, the school community must participate in the search for appropriate solutions that fit the students’ reality. The main objective of this dissertation is to investigate whether study of arts can be an efficient resource to leverage the meaningful learning of students who are afraid of risking writing in the initial phase of literacy. The methodology follows the qualitative model, where an experience with students from the 1st year of a private school, participated in literacy classes using arts as a methodological resource. The research begins with a discussion about success and failure in literacy, having as main sources, Fourquin, Bourdieu and Nóvoa. Following this part, the research will focus on David Ausubel’s Theory of Meaningful Learning, Henry Wallon’s Affection and the studies of Arts as Experience by John Dewey and Norberto Stori. In the penultimate chapter the sequence of classes with art as the main methodology and then an analysis in the light of the studied theorists will be presented. The result of the study proved that art can be a resource to enhance the meaningful learning of students for fear of risking writing in the literacy process.